Has governance eclipsed government? Patterns if environmental instrument selection and use in eight states and the EU - Andrew Jordan; Rüdiger K. W. Wurzel; Anthony R Zito (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2003)
Abstract Governance is a concept in good currency, but it is often used very imprecisely. In particular, there are precious few detailed empirical analyses of the precise extent to which environmental governance has eclipsed environmental government. This paper explores the governance transition by charting the deployment of so-called 'new' environmental policy instruments (NEPIs) such as voluntary agreements, eco-taxes, eco-labels and environmental management systems in eight industrialised states and the European Union (EU). The adoption of NEPIs offers a good touchstone because governance theory treats traditional ('command and control') regulation as the quintessence of government. This paper reveals that although there are many NEPIs, the overall pattern of change is highly differentiated across sectors and political jurisdictions. Crucially, most NEPI require some state involvement (i.e. 'government') and very few are entirely free of state involvement (i.e. pure 'governance'). This strongly suggests that environmental governance is at best supplementing, without actually comprehensively supplanting, government by regulatory means. Future research will need to explore the many different and complex ways in which environmental government and governance co-exist in public policy making.
Keywords: 330; environmental policy; European Union; governance; government; policy instruments; EU-Staaten; Good Governance; EU-Umweltpolitik